Peningkatan Hasil Belajar Ips Melalui Strategi Pembelajaran Bermain Bala-Bala Pada Siswa Kelas V Sd Negeri Ii Pagutan Tahun Ajaran 2015/2016 - Rahman, Habibur; , Drs. Rubino Rubiyanto, M.Pd; , Drs. Mulyadi S. K., SH.,M.Pd (2017)
The purpose of this research is to improve the result of science social learning preparation the independence of indonesia using the strategies learning play bala-bala to their students SD Negeri II Pagutan 2015/2016 The research is research class action, with collaboration between researchers and grade teachers. Subjects research is teachers and students 17 grade V SD Negeri II Pagutan Manyaran Wonogiri. This research consisting 2 cycles, every cycle consisting of four stages, including planning, action, observation and reflection. Data collection techniques used is observation, tests, interviews and documentation. To meet data validity the use writers validity instruments and review informants. Analysis techniques the data used was reduction data, share of data and withdrawal conclusion. The initial conditions before the cycle the results that only 8 students from 17 students who get a fulfilling KKM (≥ 65) or by 46,16%. In the cycle i first meeting study results obtained, 7 students from 17 students who get a fulfilling KKM (≥ 65) or by 41,18 %. In the cycle I meeting II study results students increased by of 7 to 11 students or by 64,70 % fulfilling KKM (≥ 65) .In the cycle II meeting student learning I the result of increased by of 11 to 13 students or by 76,47 % fulfilling KKM (≥ 65) .In the cycle II meeting II study results students increased by of 13 to 15 students or by 88,24 % fulfilling KKM (≥65) based on the research done it can be concluded that the implementation of learning bala-bala strategy play in the lessons social science grade V SD Negeri II Pagutan Manyaran Wonogiri Teaching Year 2015/2016.